An analysis of a temperature change in a cross-section of borehole heat exchanger - Złotkowski, Albert; Szczesiul, Patrycja (My University, 2013)
Underground heat exchangers (BHE) are used witch elements to transport energy between the ground and other objects on the surface of the land. For simplification described in mathematical apparatus, they works are explain how linear heat source. The temperature is the same in all bodies of this model. This reduction to let easy describe theoretical changes temperature in BHE through transporting energy to / from rock in analytic mathematic method. The bad effect of this method is present by the same value of temperature in horizontal cross-section and along BHE. The analysis of change of temperature field in the sealing cement BHE is a possibility for numerical simulation or laboratory model. Computer simulation needed according energy transport law. It to say about quantity of energy conducting between horizontal cross-section of BHE cells, on which is divided. The second method obtains value of temperature points of the sealing cement. This is to be realized by sensors set up in to the horizontal cross-section of BHE of laboratory model. This is possible thanks constructed the model of cross-section of BHE.
AGH Drilling, Oil, Gas
Keywords: borehole heat exchangers; heat pump; transport of heat